ANALISIS POLA DAN AKTOR DALAM SELEKSI KANDIDASI CALON LEGISLATIF : REFLEKSI ATAS PARTAI ADIL SEJAHTERA DI ACEH - Bimby Hidayat; Muntasir; Taufik; Mulyadi (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2024)
The purpose of this study is to analyze the selection process of candidates for the Aceh Representative Council (DPRA) from the Adil Sejahtera Party (PAS) in the 2024 elections in Aceh Province. This study uses Rahat and Hazan's candidacy theory approach to reveal the dimensions, space, and actors in the selection process. This study uses a descriptive qualitative approach. Data was collected through interviews, literature studies, and supplemented with internal party documents. Data analysis used the Miles and Huberman model through the stages of reduction, presentation, and data verification. The results of the study reveal three patterns of candidate selection for DPRA members from PAS: (1) closed selection pattern; (2) exclusive and centralistic selection pattern. The dynamics of these patterns and actors show that the selection process for DPRA candidates from PAS is not entirely meritocratic but is the result of negotiations among party elites. This study concludes that the selection process for DPRA candidates from PAS is an arena of elitist power contestation. The strong influence of religious leaders in the party means that the selection of candidates is largely determined by party elites.